Yield response to row spacing, irrigation and varieties of peanut in the semiarid region of Minas Gerais, Brazil - de Oliveira, Sirlene Lopes [UNESP]; Santos, Valdomiro Junior Neres; Filho, Aroldo Gomes; Moreira, Estefson Ferreira; Costa, Tattiane Gomes; dos Reis Sales, Hamilton (My University, 2022)
Studies on the management of peanut crops in the semiarid region of Minas Gerais are scarce. Therefore, the objective was to evaluate the agronomic performance of four peanut cultivars under different irrigation systems and row spacing in northern Minas Gerais. The cultivars IAC 503, Runner IAC 886, IAC Tatu ST, and Crioula were grown at row spacing of 0.5, 0.7, and 0.9 m and irrigated or not irrigated. The following variables were evaluated: Total number of pods, number of commercial pods, number of seeds, mass of one hundred grains, grain yield index, oil content, pod yield, grain yield and oil yield. After analysis of variance, the average values were compared using the Scott-Knott method with a probability of 5%. The spacing of 0.5 m promoted higher productivity in pods, grains, and oil in both systems. Under irrigation, IAC 503 and IAC 886 were the most productive, while the cultivars did not differ under non-irrigated cultivation. Finally, irrigation resulted in an increase in grain yield of up to 50% compared to non-irrigated cultivation.
Resposta da produtividade ao espaçamento entrelinhas, irrigação e variedades de amendoim na região semiárida de Minas Gerais, Brasil
Keywords: Arachis hypogaea L; plant density; water stress